(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This study was designed to investigate the Effect of plyometric training on selected physical and physiological variables among physical education students in volleyball players. 30 inter-collegiate male volleyball players from Karpagam Institute of Technology, Coimbatore, were selected for the purpose of the research. Two similar classes (n=15) were randomly allocated to the subjects. Group I underwent Plyometric Training (PTG) and Group - II served as a monitoring group (CG). The experimental group was given plyometric training for 3 days per week (Monday, Wednesday and Monday). The physical parameters of speed (50 mts dash), leg explosive power (vertical jump) and physiological parameters (Breath Holding Time, Resting Heart Rate) before and after training period. The data collected from the subjects was statistically analyzed with‘t’ test to find out significant improvement if any at 0.05 level of confidence. The result of the speed, leg explosive power and Breath Holding Time, Resting Heart Rate speculated significant improvement due to influence of plyometric training with the limitations of (diet, climate, life style) status and previous training. The result of the present study coincide findings of the investigation done by different experts in the field of sports sciences. Plyometric training group significantly improved speed, leg explosive power and Breath Holding Time, Resting Heart Rate college male Volleyball players.